The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10522-010-9282-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone, melatonin, oestrogens and phytoestrogens on the oxidized glutathione (GSSG)/reduced glutathione (GSH) ratio and lipid peroxidation in aged ovariectomized rats

Abstract: Ovariectomy constitutes a commonly used model in rats and mice for human menopause. After ovariectomy, an imbalance between oxidant production and antioxidant levels appears in favour of the former, with increased oxidative stress and consequently an acceleration of ageing. In the present work, the levels of reduced glutathione (GSH), a relevant antioxidant, and oxidized glutathione (GSSG), an oxidant compound, as well as lipid peroxidation (through malondialdehyde (MDA) levels), were studied in liver, heart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 68 publications
4
34
1
1
Order By: Relevance
“…Sex hormones produce a natural antioxidant effect. The sudden withdrawal of these enzymes, especially estrogens, as a result of having an ovariectomy, weakens the balance of the oxidant/antioxidant system [20,21]. In our study, the ovariectomy procedure resulted in an increase in the amount of CAT and SOD but a decrease in the amount of antioxidants such as GSH.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Sex hormones produce a natural antioxidant effect. The sudden withdrawal of these enzymes, especially estrogens, as a result of having an ovariectomy, weakens the balance of the oxidant/antioxidant system [20,21]. In our study, the ovariectomy procedure resulted in an increase in the amount of CAT and SOD but a decrease in the amount of antioxidants such as GSH.…”
Section: Discussionmentioning
confidence: 57%
“…Urata et al [32] reported that estradiol was directly linked to GSH synthesis. Therefore, ovariectomy and the subsequent estrogen loss might have significantly altered this stimulatory effect of estradiol on GSH synthesis [20]. In the present investigation, ovariectomy triggered an imbalance in the pro-oxidant status of GSH in the heart tissues of the rats.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations